Starting Neurohormonal Antagonists in Patients with Acute Heart Failure with Mid-Range and Preserved Ejection Fraction. (14th October 2021) - Seko, Y; Kato, T; Morimoto, T; Yaku, H; Inuzuka, Y; Tamaki, Y; Ozasa, N; Shiba, M; Yamamoto, E; Yoshikawa, Y; Yamashita, Y; Kitai, T; et al.
Abstract: Background: The clinical benefits of neurohormonal antagonist in patients with heart failure (HF) with mid-range and preserved ejection fraction (HFmrEF and HFpEF) were uncertain. This study aimed to evaluate the prognostic effect of starting angiotensin-converting enzyme inhibitors (ACE-I) / angiotensin II receptor blockers (ARB) and β-blocker during HF hospitalization in these patients. Methods: We analyzed 858 consecutive patients with HFmrEF (EF:40–49%) or HFpEF (EF≥50%), who were hospitalized for acute decompensated HF, were discharged alive, and were not taking ACE-I/ARB or β-blockers at admission. The study population was classified into four groups according to the status of prescription of ACE-I/ARB and β-blocker at discharge: no neurohormonal antagonist (N=342, 39.9%), ACE-I/ARB only (N=128, 14.9%), β-blocker only (N=189, 22.0%), and both ACE-I/ARB and β-blocker (N=199, 23.2%) groups. The primary outcome measure was a composite of all-cause death or HF hospitalization. Results: The cumulative 1-year incidence of the primary outcome measure was 41.2% in the no neurohormonal antagonist group, 34.0% in the ACE-I/ARB only group, 28.6% in the β-blocker only group, and 16.4% in the both ACE-I/ARB and β-blocker group (P<0.001). Compared with the no neurohormonal antagonist group, the both ACE-I/ARB and β-blocker group were associated with a significantly lower risk for a composite of all-cause death or HF hospitalization (HR: 0.59, 95% CI: 0.38–0.91, P=0.02). Conclusions: In hospitalized patients with HFmrEF and HFpEF, starting both ACE-I/ARB and β-blocker was associated with a reduced risk of a composite of all-cause death or HF hospitalization compared with not starting ACE-I/ARB or β-blocker. Funding Acknowledgement: Type of funding sources: None.